Artistic rendering in computer graphics - Lim, Florence Ming Hien. (2011)
Artistic rendering is an emerging form of art technique in computer graphics which converts photographs into artistic images. There are many existing image processing software available that performs artistic rendering such as stroke-based or region-based rendering techniques, water colouring, pen and ink stroke, oil painting, cartoon rendering and etc. However, there are very few image processing software that provide different styles of edge detection for stroke distribution in artistic rendering.